Principles of sustainable energy systems - Kutscher, Charles F.; Milford, Jana B.; Kreith, Frank (Mechanical and aerospace engineering (CRC Press), 2019)
PRINCIPLES OF SUSTAINABLE ENERGY SYSTEMS, Third Edition, surveys the range of sustainable energy sources and the tools that engineers, scientists, managers, and policy makers use to analyze energy generation, usage, and future trends. The text provides complete and up-to-date coverage of all renewable technologies, including solar and wind power, biofuels, hydroelectric, nuclear, ocean power, and geothermal energy. The economics of energy are introduced, with the SAM software package integrated so students can explore the dynamics of energy usage and prediction. Climate and environmental factors in energy use are integrated to give a complete picture of sustainable energy analysis and planning.